PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII3 SMP NEGERI 11 PEKANBARU - Firmantara, Bima; Siregar, Syarifah Nur; ', Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This research aims by the students’math achievement at class VIII.3 SMPN 11Pekanbaru, there are 14 students’ or 37,8% achieving passing grade from 37 on the main discussion about Teorema Pythagoras Pythagoras theorem and then the learning process still teacher center. The research was classroom action research. This research is aims to increase learning process and students’ math achievement at class VIII.3 SMPN 11 Pekanbaru in circle, through the implentation cooperative learning type Two Stay Two Stray. The subject are 37 students from class VIII.3 SMPN 11 pekanbaru consist of 18 male and 19 female students with the heterogenous. The collecting of the data instruments are observation and math achivement testThe research analyze by descriptive and qualitative, but students’s achievement analyze by descriptive and quantitative. observationFrom the qualitative analysis showed an improvement of the learning process before action to the first cycle and cycle II. Then the results of this study showed an increase in students from basic score with percentage 37,8%, on a daily test I with the percentage of 51,4% and the percentage of daily test II with 59,5%.Based on the previous result at can be concluded that the implentation of cooperative learning type Two Stay Two Stray to improve students’ math achievement at class VIII.3 SMPN 11 pekanbaru of circle main topic of second semester 2013/2014.Key Word :Students’ math Achievement, Cooperative Learning Type Two Stay Two Stray, Classroom Action Research.